2012
DOI: 10.1080/09518398.2011.594818
|View full text |Cite
|
Sign up to set email alerts
|

Mexican parents’ and teachers’ literacy perspectives and practices: construction of cultural capital

Abstract: This article examines the relationships among the literacy practices engaged in by first-grade children and parents at home and the ways in which these practices are communicated, shaped, and fostered by teachers and administrators in two different sociocultural environments in urban Mexico. The differences observed between the home literacy experiences of children in a working class and a middle class community included transgenerational communication of assumptions regarding literacy and schooling, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 19 publications
3
27
0
1
Order By: Relevance
“…Cultivation transforms as knowledge through practices and a process of customizing: identification and integration into a person. Regarding a practical setting of daily behaviors, research has examined attitude for dietary selection (Fismen, Samdal, & Torsheim, ), values for drinking alcohol (Allan, Clifford, Ball, Alston, & Meister, ), smoking (Haines, Poland, & Johnson, ; Reese, Arauz, & Bazan, ), and a belief in comprehensive health behaviors (Pinxten & Lievens, ). These inbuilt values, beliefs, and attitudes suggest various definitions of “health.” Therefore, practical knowledge constitutes a concept of health.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultivation transforms as knowledge through practices and a process of customizing: identification and integration into a person. Regarding a practical setting of daily behaviors, research has examined attitude for dietary selection (Fismen, Samdal, & Torsheim, ), values for drinking alcohol (Allan, Clifford, Ball, Alston, & Meister, ), smoking (Haines, Poland, & Johnson, ; Reese, Arauz, & Bazan, ), and a belief in comprehensive health behaviors (Pinxten & Lievens, ). These inbuilt values, beliefs, and attitudes suggest various definitions of “health.” Therefore, practical knowledge constitutes a concept of health.…”
Section: Resultsmentioning
confidence: 99%
“…A rubric constitutes everything from behavior to customs and is based on cultivation and is affected by norms: this is (Kamphuis, Jansen, Mackenbach, & van Lenthe, 2015). Other research has defined norms as long-lasting dispositions of the mind and body (Kamphuis et al, 2015;Reese et al, 2012), integrated parts of the person (Newman et al, 2013), or guides to what individuals regard as important in life (Kamphuis et al, 2015;Reese et al, 2012). Regarding daily life, research has examined such norms as young people's healthy eating (Fismen et al, 2012); drinking alcohol (Allan et al, 2012); and orientation about higher education, job opportunities, and careers (Royal, 2012).…”
Section: Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work DiMaggio primarily operationalizes cultural capital as "elite status" [6] or "highbrow" [7] culture, and found strong evidence of school performance effects. This interpretation was well received and has since been expanded [8] [9].…”
Section: Cultural Capitalmentioning
confidence: 85%
“…For instance, parents who had a more difficult time personally learning English were more likely to use more English than Spanish with their children, indicating that they did not want their children to struggle like they did. Reese, Mejía Arauz, and Bazán (2012) also found that Latino parents' transmit experiences to their children that mirror their own educational history. Teachers would benefit from an awareness of this influential factor.…”
Section: Beliefs About Language Developmentmentioning
confidence: 91%